Value of miR-2355-3p，miR-337-3p and miR-99a-5p detection in early screening of head and neck squamous cell carcinoma - LIU Jinghao, GUO Haiyan, GAN Guifang, CHEN Fuxiang (Zhenduanxue lilun yu shijian)
Objective To explore the value of miR-2355-3p, miR-337-3p, and miR-99a-5p in the early screening of head and neck squamous cell carcinoma (HNSCC). Methods Serum samples and clinicopathological data were collected from 60 newly diagnosed HNSCC patients (HNSCC group) and 60 healthy individuals (normal control group) who visited the Ninth People's Hospital Affiliated to Shanghai Jiao Tong University School of Medicine between July 2023 and July 2024. The relative expression levels of miR-2355-3p, miR-337-3p, and miR-99a-5p were determined using parallel detection. The HNSCC screening and diagnostic efficacy of these three miRNAs was evaluated using receiver operating characteristic (ROC) curves. Results Compared with the normal control group, serum levels of miR-2355-3p and miR-337-3p were significantly upregulated in the HNSCC group (P<0.001), while miR-99a-5p was significantly downregulated (P=0.002). The expression levels of miR-2355-3p and miR-337-3p differed significantly among HNSCC patients with tumor size >2 cm versus ≤2 cm, clinical stage Ⅰ–Ⅱ versus stage Ⅲ–Ⅳ, and with versus without cervical lymph node metastasis (P<0.05). However, no significant differences in miRNA expression were found across different age or gender groups (P>0.05). The optimal cutoff values for diagnosing HNSCC were 0.0867 for miR-2355-3p, 0.1031 for miR-337-3p, and 0.1251 for miR-99a-5p, with corresponding areas under the curve (AUCs) of 0.892, 0.877, and 0.686, respectively. The combined detection of the three miRNAs yielded an AUC of 0.954, significantly higher than those of individual markers (P<0.05) and the combination of miR-2355-3p and miR-337-3p (AUC=0.898, P<0.05). The AUC for the combined detection in early-stage (stage Ⅰ–Ⅱ) HNSCC was 0.923. Conclusions miR-2355-3p and miR-337-3p are associated with the tumor stage, size, and lymph node metastasis of HNSCC. The combined detection of miR-2355-3p, miR-337-3p, and miR-99a-5p may serve as a potential method for early screening of HNSCC.